In situ lignocellulosic unlocking mechanism for carbohydrate hydrolysis in termites: crucial lignin modification - Singh Deepak; Laskar Dhrubojyoti D; Ke Jing; Chen Shulin (Biotechnology for Biofuels, 2011)
Abstract Background Termites are highly effective at degrading lignocelluloses, and thus can be used as a model for studying plant cell-wall degradation in biological systems. However, the process of lignin deconstruction and/or degradation in termites is still not well understood. Methods We investigated the associated structural modification caused by termites in the lignin biomolecular assembly in softwood tissues crucial for cell-wall degradation. We conducted comparative studies on the termite-digested (i.e. termite feces) and native (control) softwood tissues with the aid of advanced analytical techniques: 13C crosspolarization magic angle spinning and nuclear magnetic resonance (CP-MAS-NMR) spectroscopy, flash pyrolysis with gas chromatography mass spectrometry (Py-GC/MS), and Py-GC-MS in the presence of tetramethylammonium hydroxide (Py-TMAH)-GC/MS. Results The 13C CP/MAS NMR spectroscopic analysis revealed an increased level of guaiacyl-derived (G unit) polymeric framework in the termite-digested softwood (feces), while providing specific evidence of cellulose degradation. The Py-GC/MS data were in agreement with the 13C CP/MAS NMR spectroscopic studies, thus indicating dehydroxylation and modification of selective intermonomer side-chain linkages in the lignin in the termite feces. Moreover, Py-TMAH-GC/MS analysis showed significant differences in the product distribution between control and termite feces. This strongly suggests that the structural modification in lignin could be associated with the formation of additional condensed interunit linkages. Conclusion Collectively, these data further establish: 1) that the major β-O-4' (β-aryl ether) was conserved, albeit with substructure degeneracy, and 2) that the nature of the resulting polymer in termite feces retained most of its original aromatic moieties (G unit-derived). Overall, these results provide insight into lignin-unlocking mechanisms for understanding plant cell-wall deconstruction, which could be useful in development of new enzymatic pretreatment processes mimicking the termite system for biochemical conversion of lignocellulosic biomass to fuels and chemicals.